Formulation and physical quality test of Kerinci Arabica Coffee: Skin waste scrub preparation - Muin, Dona Muin; Sabarudin, Sabarudin; Salmah, Salmah (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2025)
Background: Scrubs are traditional cosmetic preparations that are prescribed for generations and are used to remove dead skin cells, impurities and open pores so that air exchange is free and the skin becomes brighter and whiter Previous phytochemical research shows that the bioactive properties of Kerinci Arabica coffee bark consist of alkaloids, flavonoids, terpenoids, saponins and tannins, Therefore, coffee peel has great potential to be used as an ingredient for the manufacture of scrubs. The purpose of this study is to evaluate the formulation and physical quality test of scrub preparations. Method: The research method used is experimental in a laboratory with a Complete Random Design (RAL). Powder scrub formulations are made in 3 formulas with the weight of each formula being 100 g. The physical quality stability test of powder scrub preparations was carried out on the 1st, 7th and 14th days including organoleptic, moisture content, homogeneity, pH, drying time, and adhesion. Results: The test results found that during 2 weeks of storage, the scrub preparations made had met the requirements of good physical quality. In the organoleptic test, the color, shape and smell of the preparation did not change, the preparation was homogeneous, the pH was stable at 6, the moisture content was stable below 10%, the drying time test met the requirements, which was at least 15 minutes and the adhesion test was in accordance with the requirements, which was greater than 1 second. Conclusion: Formulation and physical test of Kerinci Arabica Cofee Scrub was great.